2016
DOI: 10.1371/journal.pone.0163058
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Phospholipid Biosynthesis by Gene-Encoded Enzymes Reconstituted in Liposomes

Abstract: The goal of bottom-up synthetic biology culminates in the assembly of an entire cell from separate biological building blocks. One major challenge resides in the in vitro production and implementation of complex genetic and metabolic pathways that can support essential cellular functions. Here, we show that phospholipid biosynthesis, a multiple-step process involved in cell membrane homeostasis, can be reconstituted starting from the genes encoding for all necessary proteins. A total of eight E. coli enzymes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 51 publications
1
105
1
Order By: Relevance
“…In particular, Luisi and co-workers assembled a four-enzyme cascade for phosphatidylcholine (PC) synthesis and deduced its incorporation into the membrane based on geometrical considerations (eventually the liposome size decreased, which was ascribed to the higher spontaneous curvature triggered by the newly synthesized short-chain PC-a partially undesired outcome with respect to growth). [96] Although the authors did not specifically follow the vesicle growth, they identified practical barriers causing the low lipid synthesis rate, speculated about transport mechanisms for acyl-CoA, and discussed relevant crowding and confinement effects. In another study, the synthesis of phosphatidic acid by acyltransferases, expressed via cell-free methods in vesicles, was demonstrated but no growth was observed.…”
Section: Growth Via Uptake Of Synthesized Membrane Componentsmentioning
confidence: 99%
“…In particular, Luisi and co-workers assembled a four-enzyme cascade for phosphatidylcholine (PC) synthesis and deduced its incorporation into the membrane based on geometrical considerations (eventually the liposome size decreased, which was ascribed to the higher spontaneous curvature triggered by the newly synthesized short-chain PC-a partially undesired outcome with respect to growth). [96] Although the authors did not specifically follow the vesicle growth, they identified practical barriers causing the low lipid synthesis rate, speculated about transport mechanisms for acyl-CoA, and discussed relevant crowding and confinement effects. In another study, the synthesis of phosphatidic acid by acyltransferases, expressed via cell-free methods in vesicles, was demonstrated but no growth was observed.…”
Section: Growth Via Uptake Of Synthesized Membrane Componentsmentioning
confidence: 99%
“…For that, a cell‐free synthesis system was employed for the manufacturing of collectively eight E. coli enzymes for acyl transfer and headgroup alterations, and co‐translationally reconstituted within liposomes. Such potential for ex vivo and protein purification‐free manufacturing of nonnatural and natural lipids by gene‐based lipid biosynthesis offers the potential for division and growth of an artificial cell (Scott et al, 2016).…”
Section: Cfps: Latest Platforms and Applications In Biotechnology Andmentioning
confidence: 99%
“…But this approach is nonideal for establishing a continuous artificial cell cycle since it changes the lipid composition and the membrane properties of the vesicle. Attempts are being made to incorporate the lipid synthesis machinery within liposomes in order to achieve controlled growth of synthetic cells or reconstituting the genetic pathway for lipid synthesis using a cell‐free expression system, albeit without realizing significant growth so far . The challenge has also been approached by using synthetic amphiphiles and phospholipid analogues, as well as by using autocatalytic reactions to continuously drive membrane synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts are being made to incorporate the lipid synthesis machinery within liposomes in order to achieve controlled growth of synthetic cells [34][35][36][37] or reconstituting the genetic pathway for lipid synthesis using a cell-free expression system, albeit without realizing significant growth so far. [38] The challenge has also been approached by using synthetic amphiphiles and phospholipid analogues, as well as by using autocatalytic reactions to continuously drive membrane synthesis. [39][40][41] These various attempts at growing vesicles have shown good promise, but the final aim has not been achieved as of yet and highlight the challenging nature of membrane growth, [11] especially for pure liposomes.…”
Section: Introductionmentioning
confidence: 99%